Bacterial biofilm prevalence in dental unit waterlines: a systematic review and meta-analysis - Mojtaba Bayani; Kiyavash Raisolvaezin; Amir Almasi-Hashiani; Seyed Hamed Mirhoseini (BMC, 2023)
Abstract Backgrounds Numerous studies have shown that dental unit water lines (DUWLs) are often contaminated by a wide range of micro-organisms (bacteria, fungi, protozoa) and various prevalence have been reported for it in previous studies. Therefore, this review study aims to describe the prevalence of bacterial biofilm contamination of DUWLs. Methods This is a systematic review and meta-analysis in which the related keywords in different international databases, including Medline (via PubMed) and Scopus were searched. The retrieved studies were screened and the required data were extracted from the included studies. Three standard methods including American Dental Association (ADA), The Center for Disease Control and Prevention (CDC) and contaminated > 100 CFU/ml(C-100) standards were used to assess the bacterial biofilm contamination of DUWLs. All studies that calculated the prevalence of bacterial biofilm contamination of DUWLs, and English full-text studies were included in the meta-analysis. Studies that did not have relevant data or used unusual laboratory methods were excluded. Methodological risk of bias was assessed by a related checklist and finally, the data were pooled by fixed or random-effect models. Results Seven hundred and thirty-six studies were identified and screened and 26 related studies were included in the meta-analysis. The oldest included study was published in 1976 and the most recent study was published in 2020. According to the ADA, CDC and C-100 standards, the prevalence of bacterial contamination was estimated to be 85.0% (95% confidence interval (CI): 66.0-94.0%), 77.0% (95%CI: 66.0-85.0%) and 69.0% (95%CI: 67.0-71.0%), respectively. The prevalence of Legionella Pneumophila and Pseudomonas Aeruginosa in DUWLs was estimated to be 12.0% (95%CI: 10.0-14.0%) and 8.0% (95%CI: 2.0-24.0%), respectively. Conclusion The results of this review study suggested a high prevalence of bacterial biofilm in DUWLs; therefore, the use of appropriate disinfecting protocol is recommended to reduce the prevalence of contamination and reduce the probable cross-infection.